The effect of the listener in directing the letters of meanings in The Holy Quran - Abbas, Shifaa Khudair (Al-Adab Journal, 2021)
The speaker and the listener form the basis of the communicative process, this study came to highlight the impact of the listener in directing the meanings of letters in The Holy Quran, and the changing connotations that they have, and its role in responding to the listener and achieving communication, taking into account his conditions.